Trends and research foci in immunoregulatory mechanisms of allergic rhinitis: a bibliometric analysis (2014-2024) - Wang, Yandan; Zhang, Liangran; Shi, Baoyuan; Luo, Junpeng (Frontiers in Immunology, 2024)
Background: This study aims to provide a comprehensive bibliometric analysis of research trends, hotspots, and future directions in the immunoregulatory mechanisms of allergic rhinitis (AR) from 2014 to 2024. Methods: Data were sourced from the Web of Science Core Collection (WoSCC), covering articles and reviews published between April 1, 2014, and March 31, 2024. The search terms included "Allergic Rhinitis," "AR," and related terms along with specific keywords related to immune cells and inflammatory mediators. Bibliometric tools such as CiteSpace, VOSviewer, and SCImago Graphica were used to analyze institutional cooperation networks, keyword co-occurrence, citation bursts, and research topic evolution. Microsoft Excel 2019 was employed to display annual publication trends. Results: A total of 2200 papers met the inclusion and exclusion criteria. The number of publications showed an upward trend over the past decade, with a significant peak in 2021. China (583 papers) and the United States (454 papers) were the major contributing countries. Imperial College London emerged as the leading institution. Key research frontiers identified include the roles of NF kappa B and air pollution in AR. Keyword burst analysis revealed emerging topics such as respiratory allergy and personalized treatment strategies. Notable limitations include the exclusive use of the WoSCC database and the restriction to English-language publications.The field of immunoregulatory mechanisms in allergic rhinitis has seen significant growth, with China and the United States leading the research. Future research should focus on developing personalized treatment plans and understanding the comprehensive impact of environmental factors. Continued interdisciplinary collaboration and international cooperation will be essential for advancing therapeutic strategies in AR.